Mid-Air haptic sensations produced by ultrasound actuators in patients with carpal tunnel syndrome - Akdağ, Mehmet Akif. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2023., 2023)
This thesis utilizes psychophysical experiments with mid-air haptic ultrasound actuators to assess carpal tunnel syndrome (CTS) patients’ tactile sensation. 19 female and one male patients (age: 33-61) with unilateral CTS took part in the experiments. We used a two-alternative forced choice task experiments to measure detection thresh olds around 250 Hz modulation frequency at the thenar eminence (TE) and at the index finger in affected and healthy hands. In addition, 15 female CTS patients par ticipated in a virtual reality-assisted hand exercise game with haptic feedback. The system usability scale (SUS) and exercise performance scores were evaluated. There was no significant difference in the threshold values from the TE between the CTS hand (M=0.85 au, SD=0.15) and the healthy hand (M=0.87 au, SD=0.16). The thresholds measured from the index fingers of CTS affected hands were all higher than the maxi mum stimulus level that could be produced by the ultrasonic actuators. For the healthy hands of 17 patients, the detection thresholds were (M=0.90 au, SD=0.09), and the remaining 3 had threshold values above the maximum output of the device. For the exercise game results, there was a significant correlation (ρ = 0.89, p < 0.001) between the SUS (M=80.17%, SD=18.33) and performance scores (M=83.31%, SD=14.80). Since the CTS was at an early stage and there may be a branching (palmar cutaneous branch) of the nerve before entering the carpal tunnel, thresholds were found similar in both hands at the TE. Unfortunately, the limitations of the haptic device did not allow a comparison between index fingers. Moreover, this device and novel technology may be used for the follow-up of the rehabilitation and the treatment of the CTS. As such, the usability of the system is above the criterion value, and in the future it can be improved not to be affected from the performance in the exercise games. NOTE Keywords: Touch, Psychophysics, Somatosensory System, Carpal Tunnel Syndrome, Pacinian Channel, Ultrasound Stimulus, Mid-Air Haptics.
Keywords: Carpal tunnel syndrome.; Touch.; Somatosensory neurons.